2007
DOI: 10.1901/jaba.2007.177-05
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Report and Direct Assessment of Preferences for Identifying Reinforcers for Young Children

Abstract: Teachers were asked to identify and rank 10 preferred stimuli for 9 toddlers, and a hierarchy of preference for these items was determined via a direct preference assessment. The reinforcing efficacy of the most highly preferred items identified by each method was evaluated concurrently in a reinforcer assessment. The reinforcer assessment showed that all stimuli identified as highly preferred via the direct preference assessment and teacher rankings functioned as reinforcers. The highest ranked stimuli in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 17 publications
3
46
0
Order By: Relevance
“…Moreover, several studies have examined how effective caregiver-chosen items function as reinforcers in human populations (Cote, Thompson, Hanley, & McKerchar, 2007;Didden & de Moor, 2004). A common finding is that even though caregiver-identified items will usually function as reinforcers, they may not be optimal.…”
Section: The Value Of Systematic Testingmentioning
confidence: 99%
“…Moreover, several studies have examined how effective caregiver-chosen items function as reinforcers in human populations (Cote, Thompson, Hanley, & McKerchar, 2007;Didden & de Moor, 2004). A common finding is that even though caregiver-identified items will usually function as reinforcers, they may not be optimal.…”
Section: The Value Of Systematic Testingmentioning
confidence: 99%
“…These studies included the comparisons between the personnel views and the single-stimulus preference assessment (Green et al, 1988), the caregivers" predictions and the paired-stimulus preference assessment , the personnel predictions and the paired-stimulus preference assessment ( Newton et al, 1993), the parents" and teachers" views and the paired-stimulus direct preference assessment (Didden and Moor, 2004), the teacher and familiar personnel views and the single-stimulus direct preference assessment (Spevack, 2006), the caregivers" views and the direct observation data (LaRosa, 2007), the teacher reports and the paired-stimulus direct preference assessment (Cote et al, 2007), the multiple-stimulus without replacement and the teachers" preference assessment (Resetar and Noell, 2008), and the caregivers" views and the multiplestimulus without replacement (Waldvogel and Dixon, 2008). As it is evident from the mentioned studies, there was no study that compared the indirect preference assessment to the directly applied three assessment methods.…”
Section: Preference Assessmentmentioning
confidence: 99%
“…Stimuli identified as "low preference" by the direct assessment did not generally function as reinforcers, regardless of their classification by the indirect assessment. Other researchers have demonstrated that caregiver reports may not correlate perfectly with observation-based measures of preference, and that conducting direct SPAs increases the likelihood of identifying the most potent reinforcer (e.g., Cote, Thompson, Hanley, & McKerchar, 2007). Caregiver opinions are ideally coupled with direct SPAs to identify the most potent reinforcers for a particular client (Cote et al), and asking caregivers to identify potential reinforcers is an effective way to select stimuli for subsequent SPAs (e.g., Fisher, Piazza, Bowman, & Amari, 1996).…”
Section: Preference Assessment Practicesmentioning
confidence: 99%